2009
DOI: 10.1074/jbc.m109.008938
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Induced Pluripotent Stem Cell Lines from Tibetan Miniature Pig

Abstract: Induced pluripotent stem cell (iPS) technology appears to be a general strategy to generate pluripotent stem cells from any given mammalian species. So far, iPS cells have been reported for mouse, human, rat, and monkey. These four species have also established embryonic stem cell (ESC) lines that serve as the gold standard for pluripotency comparisons. Attempts have been made to generate porcine ESC by various means without success. Here we report the successful generation of pluripotent stem cells from fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
351
3
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(380 citation statements)
references
References 35 publications
(42 reference statements)
15
351
3
11
Order By: Relevance
“…Gene targeting by homologous recombination is extremely inefficient in porcine somatic cells 3 , and porcine embryonic stem cells (ES) have not yet been established 15 . Recently, several groups described the derivation of porcine induced pluripotent cells (iPS) [16][17][18][19][20] , however, only low chimerism has been found after blastocyst complementation experiments 21,22 . The employment of porcine iPS cells in the SCNT method resulted in extremely low rates of born piglets 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Gene targeting by homologous recombination is extremely inefficient in porcine somatic cells 3 , and porcine embryonic stem cells (ES) have not yet been established 15 . Recently, several groups described the derivation of porcine induced pluripotent cells (iPS) [16][17][18][19][20] , however, only low chimerism has been found after blastocyst complementation experiments 21,22 . The employment of porcine iPS cells in the SCNT method resulted in extremely low rates of born piglets 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Through iterative experiments, they eventually found that all factors save four were dispensable for reprogramming-these four factors became known as the classical quartet of pluripotential reprogramming factors; Oct4, Sox2, Klf4, and c-Myc (Takahashi and Yamanaka, 2006). This classical cocktail of reprogramming factors has been shown to induce pluripotency within a multitude of mouse cell types, as well as rhesus monkey (Li et al, 2009b;Liao et al, 2009), pig (Esteban et al, 2009;Ezashi et al, 2009;Wu et al, 2009;West et al, 2010) and human cells (Takahashi et al, 2007;Yamanaka, 2007).…”
Section: Reprogramming With Different Factors Of Transcription Factorsmentioning
confidence: 99%
“…Despite this, pluripotent stem cell lines for the rat, pig and monkey in the form of iPSC lines have been derived through the overexpression of Oct4, Sox2, Klf4, and c-Myc from these species Esteban et al, 2009;Ezashi et al, 2009;Li et al, 2009b;Liao et al, 2009;Wu et al, 2009). However, we note that some caution must be taken when considering these iPSC lines from such species, because the pluripotential character of such species' iPSC lines is not comparable with the pluripotent character of conventional mouse ES and iPSC cell lines.…”
Section: Reprogramming With Different Factors Of Transcription Factorsmentioning
confidence: 99%
See 2 more Smart Citations